2015
DOI: 10.4034/rbcs.2015.19.02.12
|View full text |Cite
|
Sign up to set email alerts
|

Desafios Enfrentados por Mulheres Primigestas em Idade Avançada

Abstract: 2 RESUMOObjetivo: Analisar a associação entre idade materna avançada e as possíveis complicações na gestação, tanto materna quanto fetal, à luz da produção científica brasileira. Material e Métodos: Trata-se de uma revisão da literatura na base de dados Biblioteca Virtual de Saúde na qual foram cruzados os descritores: complicações na gravidez e idade materna. Como critérios de inclusão para este estudo estabeleceram-se: artigos originais; estudos com abordagem qualitativa ou quantitativa; publicações escritas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
8

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 6 publications
0
12
0
8
Order By: Relevance
“…The women who had a comorbidity prior to pregnancy had a lower frequency of maternal complications, which is surprising since studies found that age-related diseases are determining factors for the occurrence of adverse effects in these women (5)(6) . The pregnant women who had some preexisting condition were probably in treatment and needed greater care and attention, so they were more eager to attend prenatal consultations.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…The women who had a comorbidity prior to pregnancy had a lower frequency of maternal complications, which is surprising since studies found that age-related diseases are determining factors for the occurrence of adverse effects in these women (5)(6) . The pregnant women who had some preexisting condition were probably in treatment and needed greater care and attention, so they were more eager to attend prenatal consultations.…”
Section: Discussionmentioning
confidence: 94%
“…This finding is explained by the gradual decline in fertility up to the age of 35 followed by a sharper decline after this age. As the age advances, the likelihood of structural defects in the ova and the frequency of chronic disease also increases, and as the age of the pregnant woman increases, the reproductive history gets progressively more complicated (5) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Taking into account these significant physiological and emotional changes that affect the body and mind of pregnant women, and consequently their interaction with the world, it is important that women have adequate follow-up by family and health professionals, considering that in addition to discomfort there may be many risks associated with pregnancy, leading to possible complications for both the mother and the fetus, and subsequently for the newborn (1)(2) . In this sense, it is necessary that women have access to quality and humanized prenatal care based on the best scientific evidence in order to provide timely interventions to ensure the health of the (mother-baby) binomial, thereby enabling early detection of health problems and consequently their timely treatment and avoiding complications during pregnancy and childbirth (3)(4) , thus contributing to reduced maternal mortality, which still has high occurrence.…”
Section: Introductionmentioning
confidence: 99%